PENGEMBANGAN FORMULA ENTERAL GUDLEAI DIA PRO+ BERPROTEIN TINGGI BERBASIS KACANG KEDELAI, WHEY PROTEIN ISOLATE, DAN KACANG GUDE UNTUK PASIEN DIABETES MELITUS - Widiasih, Wida; Judiono, Judiono; Priawantriputri, Witri; Saleky, Yohannes Willihelm (Jurusan Gizi Poltekkes Kemenkes Bandung, 2025)
Malnutrition is a common condition among patients with type 2 diabetes mellitus (T2DM), primarily caused by metabolic dysregulation, unbalanced dietary patterns, diabetes-related complications, and recurrent infections. Adequate intake of high-quality protein plays a crucial role in preventing malnutrition in this population. This study aimed to develop and evaluate a high-protein enteral formula based on soybeans, whey protein isolate, and pigeon pea as a potential nutritional intervention for T2DM patients without renal impairment. The evaluation included assessments of organoleptic properties, macronutrient composition, dietary fiber content, antioxidant activity, energy density, flow rate, shelf life, and economic feasibility. An experimental design was employed, involving 15 trained panelists for sensory analysis. The Mann–Whitney test revealed significant differences between formulas F1 and F3 in terms of taste and aroma (p < 0.05), with no significant differences in color, consistency, or overall acceptance (p > 0.05). Formula F2 demonstrated superior sensory attributes compared to F3 in all evaluated aspects (p < 0.05). Proximate and antioxidant analyses of the optimized formula (F2 - Gudelai Dia Pro+) showed an energy content of 273 kcal, protein 16.22 g, fat 9.14 g, carbohydrates 31.47 g, dietary fiber 2.51 g, and antioxidant activity of 150.12 µg/ml. The formula exhibited an energy density of 1.31 kcal/cc and a flow rate of 1.06 ml/sec. Shelf-life testing indicated a decline in quality after 12 hours at room temperature. Cost analysis revealed that Gudelai Dia Pro+ had a production cost of IDR 11,165 per serving, making it more cost-effective than commercial enteral formulas by a margin of IDR 1,835